Coupling multicomponent droplet evaporation and tabulated chemistry combustion models for large-eddy simulations. (January 2017) - Mahiques, E.I.; Dederichs, S.; Beck, C.; Kaufmann, P.; Kok, J.B.W.
Highlights: The Lewis fugacity rule gives good results at low temperatures and moderate pressures. A water diffusivity model is introduced for the evaporation of emulsion droplets. The chemistry tables used for the combustion model are small and compact. The combustion model is more sensitive to changes in enthalpy than in fuel fraction. Abstract: An evaporation model for multicomponent fuels and emulsions is implemented in OpenFOAM within the Euler–Lagrangian formulation. The model is suitable for pressures typical of heavy duty gas turbines, up to 30 bar, and considers an increased evaporation rate of the most volatile component when the droplet temperature reaches its boiling temperature. Evaporation of emulsion droplets is modeled following a shell approach, assuming that the water in the droplet core does not evaporate. A diffusivity model is introduced to account for the transport of the dispersed phase from the core to the outer shell. The combustion model is based on the Flamelet Generated Manifold approach. The mixture fraction is calculated from the species mass fractions to couple it with the evaporation model. Flamelet tables are created for different enthalpies and mixture fractions so that they can be used in non-premixed simulations. The thermo-chemistry model considers up to two fuel components by using 4-D tables. Experimental data for n-decane droplets are used to validate the evaporation model. Results from the combustion model are compared with the detailed chemistry solutions. Following the separate evaluation of each model, 1-D spray simulations for 0% and 10% initial water contents are performed to verify the coupling between the models, so that they can be applied to partially pre-vaporized spray flames.